2018
DOI: 10.22271/ortho.2018.v4.i1d.31
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of anthropometric measurements with bone mineral density in south Indian population

Abstract: There is no data or very limited data available about the relation between anthropometric measurements like weight and height, and bone mineral density based on sex and age of South Indian population. Identifying persons at risk of sustaining osteoporotic fractures is crucial for the prevention of fracture. Therefore the present was undertaken for the identification, prevention and timely treatment of osteoporosis. The study population consisted of 350 patients (both male and female patients). The study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
4
1
Order By: Relevance
“…However, if a T-score less than −2.5 is defined as osteoporosis, the prevalence of osteoporosis may be underestimated when BMD of the heel is measured by ultrasonic densitometry [ 23 ]. This finding may partially explain why the correlations between anthropometric parameters and BMD observed in this study differed from those in previous studies, which have found that, in addition to age, BMD significantly correlated with height, weight, and BMI [ 1 , 7 , 24 , 25 ]. Because few studies have assessed correlations among age, anthropometric parameters and BMD in Asian populations, especially in Chinese, other factors may have contributed to the differences observed.…”
Section: Discussioncontrasting
confidence: 95%
See 4 more Smart Citations
“…However, if a T-score less than −2.5 is defined as osteoporosis, the prevalence of osteoporosis may be underestimated when BMD of the heel is measured by ultrasonic densitometry [ 23 ]. This finding may partially explain why the correlations between anthropometric parameters and BMD observed in this study differed from those in previous studies, which have found that, in addition to age, BMD significantly correlated with height, weight, and BMI [ 1 , 7 , 24 , 25 ]. Because few studies have assessed correlations among age, anthropometric parameters and BMD in Asian populations, especially in Chinese, other factors may have contributed to the differences observed.…”
Section: Discussioncontrasting
confidence: 95%
“…Recently, ultrasonic densitometry measurements of BMD at the calcaneus site have been proposed for identifying individuals at risk of osteoporotic fracture in large populations. This technique has been demonstrated to be an ideal experimental tool because of its portability and lack of the risk of radiation [ 7 , 10 , 21 , 22 ]. However, if a T-score less than −2.5 is defined as osteoporosis, the prevalence of osteoporosis may be underestimated when BMD of the heel is measured by ultrasonic densitometry [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations